2004
DOI: 10.1128/jvi.78.12.6389-6398.2004
|View full text |Cite
|
Sign up to set email alerts
|

Kaposi's Sarcoma-Associated Herpesvirus Glycoprotein K8.1 Is Dispensable for Virus Entry

Abstract: Kaposi's sarcoma-associated herpesvirus (KSHV) is considered the etiologic agent of Kaposi's sarcoma and several lymphoproliferative disorders. Recently, the KSHV genome was cloned into a bacterial artificial chromosome and used to construct a recombinant KSHV carrying a deletion of the viral interferon regulatory factor

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 60 publications
5
51
0
Order By: Relevance
“…So far, gpK8.1 and gB have been identified as the heparan sulfate binding ligands on KSHV (Akula et al, 2001a;Birkmann et al, 2001;Wang et al, 2001). However, it has also been shown that gpK8.1 is not required for KSHV entry into 293 cells (Luna et al, 2004). Based on our results, it can be speculated that KCP at the surface of KSHV particles aids the initial attachment of virus to target cells by binding to glycosaminoglycans.…”
Section: Discussionsupporting
confidence: 50%
“…So far, gpK8.1 and gB have been identified as the heparan sulfate binding ligands on KSHV (Akula et al, 2001a;Birkmann et al, 2001;Wang et al, 2001). However, it has also been shown that gpK8.1 is not required for KSHV entry into 293 cells (Luna et al, 2004). Based on our results, it can be speculated that KCP at the surface of KSHV particles aids the initial attachment of virus to target cells by binding to glycosaminoglycans.…”
Section: Discussionsupporting
confidence: 50%
“…Although the exact role of K-bZIP in DNA replication is unknown, it has been shown to be upregulated by K-Rta (4). K8.1 encodes a viral structural protein that displays true lategene kinetics (17,20,28).…”
Section: Resultsmentioning
confidence: 99%
“…The recent subcloning of the HHV8 genome into a bacterial artificial chromosome (BAC) vector allowed the generation of viral deletion mutants targeting specific open reading frames (ORFs) within the virus (17,35). In this report, we generated a recombinant BAC with a deletion in the ORF50 locus (BAC36⌬50) and show that K-Rta is required for lytic DNA replication and viral growth.…”
mentioning
confidence: 99%
“…Although a KSHV BAC has been developed (40) in several studies (19,22,36,37), the major drawback of this system is the lack of an available animal model to study the infection and pathogenesis of BAC-derived viruses. This is due to the fact that KSHV does not appear to infect and produce disease in any animal system tested thus far, including primates (14,27).…”
Section: Discussionmentioning
confidence: 99%